(3fRgI GdMGOj HCNHGQ edhc GdbQf GdMGOjs - (3CHh YHO Gddg eMeO GdUZjQ Hf eMeO Hf YHO Gddg GdjaQGfj, eMeO GdUZjQ,J (B1155 (3g` s ((3eMeO Hf eMeO Hf CMeO GdOZhZj s)
(3ChdgG (B:s
(3hHYO , aEf Yde GdJGQjN ef CTQa GdYdhe hEfi de CRd efP YdbJ JejeI GdJejjR ai YVOi eJThbkG Edi CNHGQ GdOhdI GdSYOjI s
(3BNQgG (B:s
(3bGd eDdag hbO cfJ HdZJ ai GdJbjjO Yf Pdc ZGjJg hGdMeO ddg GdPi gOGfG dgPG heG cfG dfgJOi dhdG Cf gOGfG Gddg s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B67s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B457 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B681 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B448 s
Keywords: (3GdJGQjNs